Analysis of the Leadership of Mother of Paud in Early Childhood Education in Sigi Biromaru District - Haris Abd. Kadir; Rajindra Rajindra; Hazizah Hazizah; Hasmawati Hasmawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
In encouraging quality early childhood education (PAUD) services, it is hoped that PAUD mothers can join hands with all elements of society and the Sigi district government, so that the provision of early childhood education services (PAUD) is optimal. The purpose of this study was to determine and analyze the leadership of early childhood education mothers in early childhood education in Sigi Biromaru District. The results of the study illustrate that the leadership of PAUD mothers in Sigi Biromaru Subdistrict in providing directions about the care or guidance of their students has intrinsically strong motivation so that it has a positive impact on their students. It must be understood that the purpose of early childhood education is a basic foundation of education. The ability of educators to play a very important role in the development of basic abilities and the potential for children's intelligence which will influence them at higher levels.